Pengaruh Karakteristik Situasional dan Komponen Kualitas Layanan Gerai Starbucks terhadap Keputusan Pembelian Ulang - Adityo, Danny; Darmawan, Dwi Putra; Susrusa, K. Budi (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2014)
Increasing in coffee industries attract investor to invest their funds in this business field. One of investor that attracted in this field industry is Starbucks. Starbucks is known as international coffee shop that has good reputation on service quality. In this time service quality is being important things due to its affect to purchasing decision. Situational variable is another thing that affect to purchase decision. This research is aimed to know the affect of situational variable and service quality to repurchase decision at Starbucks. This research use regression analysis to measuring and knowing the affection of situational variable and service quality to repurchasing decision at Starbucks. The subject of this research is consumer of Starbucks in Bali. Based on Roscoe’s theory that stated in multivariate research sample size at least 10 times of number variables. This research use 9 variables, so minimal sample for this research is 90, but on its research the sample were added become 150 to make better result. The result of this research was developed two phase of research. In the first phase thirty amount of questionnaire were spread to the consumers to be analyzed for validity and reliability test. From 38 questions, all were stated as a valid question if its Alpha Pearson correlation was bigger than 0,3 (? ? 0,3). Reliability test result standard value r > 0,6. Cronbach’s alpha based on standarized items resulted 0,972 (> 0,6). It means the indicators were reliable and coud be spread to the respondent. The second phase, questionnaires were given to the customers and then been analyzed. From this analyzing get some result that service quality dimension variables such as tangible, reliability, responsiveness, assurance, and empathy has positive affect to repurchase decision. And for situational variable there are three variable that has positive affect to repurchase decision such as temporal perspective, task definition, and mood. Meanwhile, social surroundings didn’t give positive affect to repurchase decision.
Keywords: Situational characteristic, service quality component, Starbucks, and repurchasing decision